Changes in potential distribution and cultivation areas of Allium victorialis L. under climate change - Huang, Yi; Yang, Jian; Zhao, Guanghua; Yang, Yang; Jiaba, Wuzhi; Li, Jialin; Yang, Tingyong; Yao, Jianmin (Frontiers in Plant Science, 2025)
IntroductionClimate change has profoundly reshaped the spatiotemporal distribution patterns of plants. A. victorialis, a wild vegetable with significant edible and medicinal value, is highly favored by residents in the upper reaches of the Dadu River - Minjiang River, leading to its extensive collection and utilization.MethodsThis study simulated the potential distribution of A. victorialis in the upper reaches of the Dadu River-Minjiang River using an ensemble model, predicting the impacts of future climate change on its distribution, the migration patterns of the centroid of suitable habitats, and its ecological niche. Additionally, a production dynamic model integrating ecological suitability and nutritional components of A. victorialis was constructed to delineate its current and future potential cultivation areas.Results and discussionThe results demonstrated that the annual temperature range, precipitation in the warmest quarter, and temperature seasonality coefficient are the main factors restricting the potential distribution of A. victorialis Multivariate environmental similarity and the most dissimilar variable analysis revealed significant climate anomalies in the study area, indicating that future climate change will have a substantial impact on A. victorialis. In the current period, the suitable habitats and high-yield cultivation areas of A. victorialis are concentrated in low-altitude river valleys in the upper reaches of the Dadu River - Minjiang River. Under future scenarios, highly suitable habitats and first-class cultivation areas will face shrinkage, with the ecological niche and distribution centroid migrating northeastward. By 2090, under the SSP5-8.5 scenario, the changes will be most drastic: first-class cultivation areas will disappear entirely, and highly suitable habitats will be nearly lost. This study will facilitate the development of suitable management strategies for A. victorialis in the upper reaches of the Dadu River-Minjiang River, providing a scientific reference for the sustainable utilization of mountain plant resources under climate change.